The Role of the Lateral Soft Tissues in Controlling Anterior Translation And Internal Rotation of the Tibia, and An Investigation of Lateral Reconstructions Accompanying ACL Reconstruction. Issue 5 (31st May 2017) - Williams, Andy; Stephen, Jo; Kittl, Christoph; Inderhaug, Eivint; El-Daou, Hadi; Dodds, Alex; Halewood, Camilla; Amis, Andrew
Introduction: There is considerable current interest in the role of the lateral soft tissue structures in the context of ACL deficiency (ACLD). Of course the topic is not new but a re-visitation, although with improved experimental techniques available. It was clear that there was a rush to create surgical techniques based on the 'Anterolateral Ligament' (ALL) but without investigative 'due-diligence' and without consideration that other structures may be important, or more important. Objectives: To study the anatomy and biomechanics of the lateral soft tissues relevant to the ACL and ACL reconstruction techniques investigating isometricity, structures' contributions to resistance of anterior tibial translation (ATT), internal rotation (IR), and pivot shift (PS). Also we studied the impact of various reconstructions on restoration of kinematics and potential over-constraint and effects on articular surface compression load. Methods: Several studies were undertaken. In all healthy fresh-frozen cadaveric specimens were used. Descriptive anatomy was described. Length changes of suture fixed at structure and reconstruction attachment points on the tibia and femur were measured with linear variable displacement transducers (LVDTs). To investigate structures' contribution to resist translation and torque a 6-degrees of freedom robot with a universal force-moment sensor was used in a classic 'cutting study'. The robot replayed the same movement with sequential sectioning of structures recording the decrease in force / torque needed to reach the same movement limit. In this way the structure's resistance to motion as a percentage of the total could be calculated. In other studies knees were mounted in a test rig where knee kinematics were recorded from 0° to 100° of flexion by use of an optical tracking system. Joint surface compression was measured with Tekscan pressure-sensitive film. Results: The Anterolateral Ligament exists attaching to the tibia mid-way between the LCL attachment to the fibula and Gerdy's tubercle, and the femur proximal and posterior to the femoral LCL attachment 1 . However the most isometric structure is the ITB 2 from Gerdy's tubercle to its attachments to the distal lateral femur. The ACL is the primary restraint to resist ATT, but is only the primary restraint to IR / PS close to extension. The ITB, with its attachments to the lateral distal femur, is the most important restraint at all other angles, whilst the ALL / capsule contribute very little restraint to ATT / IR / PS at any angle 3 . ITB-based tenodeses taken deep to the LCL, irrespective of femoral attachment points, are more isometric 1 and restore kinematics more closely to normal compared to an ALL reconstruction. Fixation of the tenodeses with the knee with 0° tibial rotation, and tension of 20 N resulted in no change in tibio-femoral / patello-femoral contact pressures. Fixation with significant external rotation or excess tension (40 N) did increase contact pressures and lead to over-constraint. Conclusion: Despite recent interest the ALL is not as important to the ITB with its femoral attachments in controlling IR / PS. ITB-based tenodeses taken deep to the LCL perform well unless over-tensioned or fixed with tibial ER in the lab. The Anterolateral Ligament: Anatomy, length changes and association with the Segond fracture A. L. Dodds, C. Halewood, C. M. Gupte, A. Williams, and A. A. Amis. Bone Joint J 2014 96-B: 325-331 Length change patterns of the lateral extra-articular structures of the knee and related reconstructions. C.Kittl, C Halewood, J Stephen, Gupte C, A Weiler, A. Williams, A.A. Amis. AJSM 2015; 43(2): 354-62 The role of the anterolateral structures and the ACL in controlling laxity of the intact and ACL-deficient knee. C Kittl, H El-Daou, KK Athwal, CM Gupte, A Weiler, A Williams, AA Amis. AJSM 2016; 44: 345-354